Antibacterial and antifungal activities and phytochemical profile of leaf extract from different extractants of Ricinus communis against selected pathogens - Suurbaar, Jennifer (BMC Res Notes, 2017)
OBJECTIVES: Ricinus communis leaves are used in herbal preparations for treating candidiasis, skin and wound infections in Ghana. This study aimed at comparing the phytochemical profile of aqueous, methanol, petroleum ether, ethyl acetate and ethanolic extracts of the leaves of Ricinus communis and determine the growth inhibitory activities, bactericidal, bacteriostatic and fungicidal effects of the respective extracts on Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonaie and Candida albicans. RESULTS: The aqueous, methanol and ethanol extracts were shown to contain most of the phytochemicals analyzed. All solvents extracts exhibited inhibitory activity against the growth of all microorganisms under study. The methanol extract showed highest zones of inhibition and was found to be statistically significant (P < 0.05) compared to other solvents extracts. All solvents extracts exhibited both bacteriostatic and bactericidal effects on the test organisms at varying concentration, with MIC values ranging from 3.13 to 25.0 mg/ml and MBCs were from 200 to 400 mg/ml. MFCs of Candida albicans was between 200 and 400 mg/l. Our data confirm the anti-bacterial and anti-fungal properties of R. communis and showed that the biologically relevant phytochemicals from the leaves of this plant can be extracted with the solvents aqueous, methanol and ethanol. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-017-3001-2) contains supplementary material, which is available to authorized users.